Integrated strategy for generating permutation - Karim, Sharmila; Omar, Zurni; Ibrahim, Haslinda (Hikari Ltd, 2011)
An integrated strategy for generating permutation is presented in this paper. This strategy involves exchanging two consecutive elements to generate the starter sets and then applying circular and reversing operations to list all permutations. Some theoretical works are also presented.